Transformasi Digital Manajemen Pendidikan - Soedjono Soedjono (Universitas PGRI Semarang, 2022)
Digital transformation in education can improve instructional learning, particularly in higher education, by combining traditional classroom-based approaches with current technology. In this study paper, we will look at how the digital transformation of school management will affect the education system, how it will benefit others, and how we might use digital studies to aid future generations.